1990
DOI: 10.1007/bf00845000
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco use in adolescent females: Prevalence and psychosocial factors among racial/ethnic groups

Abstract: From a stratified, random sampling of Southeastern, nonurban high schools, survey data on smokeless tobacco use and potential psychosocial risk factors were obtained from 5683 adolescent females. Of the 15.3% who reported trying smokeless tobacco, most (75%) reported only experimental use. Factor analysis of the psychosocial items resulted in four factors: perceived negative consequences, substance use, modeling, and active lifestyle. Discriminant analysis on use indicated that modeling influences and use of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Previous studies have demonstrated cigarette smoking to be a strong correlate of both regular (CohenSmith & Severson, 1999) and lifetime (Lee et al, 1994;Riley et al, 1990) ST use in females. To our knowledge, however, the present study is the first one to demonstrate a positive association between trying clove cigarettes, pipes, and cigars and lifetime ST use among women.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies have demonstrated cigarette smoking to be a strong correlate of both regular (CohenSmith & Severson, 1999) and lifetime (Lee et al, 1994;Riley et al, 1990) ST use in females. To our knowledge, however, the present study is the first one to demonstrate a positive association between trying clove cigarettes, pipes, and cigars and lifetime ST use among women.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, females may be more secretive about their ST use than are men (Cohen-Smith & Severson, 1999), which could have led to a greater reluctance to admit to ST use. Third, we were not able to assess several factors found to be associated with both lifetime and regular ST use in past studies, including social modeling Cohen-Smith & Severson, 1999;Riley et al, 1990), participation in athletics and other outdoor activities (Cohen-Smith & Severson, 1999;Lee et al, 1994;Riley et al, 1990), and the use of ST for weight control (Cohen-Smith & Severson, 1999). Fourth, because of the limited number of current ST users, correlates of ST use were assessed based on lifetime history of chewing tobacco or snuff use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations